INTIMATE PARTNER VIOLENCE: CONSEQUENCES ON PSYCHOSOCIAL HEALTH - Domínguez Fuentes, Juan Manuel; García Leiva, Patricia; Cuberos Casado, Inmaculada (Anales de Psicología / Annals of Psychology, 2008)
Nowadays, intimate partner violence is one of the most important social problems in Spain, as in many other countries, because of high number of victims as well as the social and personal consequences. The aim of the study was to analyze the characteristics of psychosocial damage for development of social and clinical intervention with maltreated women. The sample was 100 battered women from Malaga. The instruments used were: An adaptation of Entrevista Semiestructurada para Víctimas de Maltrato Doméstico (Echeburua & Corral, 1998) and Escala de Inadaptación (Echeburúa & Corral, 1987). Data were collected using individual and voluntary interviews. The results show important consequences of maltreatment on women’s social health, specially in the following areas: relationship or possibility of getting a partner, free time and social life. This study was supported by the IX Research Grant (Malaga Mujer) of the Council of Malaga (Area de Igualdad de Oportunidades de la Mujer).